Contributions of injury deaths to changes in life expectancy and disparity: A comparative analysis of G7 countries over two decades - Firoozeh Bairami; Mohammad Hajizadeh; Ali Kiadaliri (Population Health Metrics)
Abstract Background Despite the high level of economic development in the Group of Seven (G7) countries, injury deaths remain a public health concern in these countries. This paper examines the contribution of injury deaths to changes in life expectancy (LE) and life disparity (LD) in the G7 countries. Methods We used annual data from the WHO mortality database to compute LE and LD during 2001-03 and 2017-19. The contributions of injury deaths to LE and LD changes for each sex were decomposed by age and cause using a continuous-change model. Results Across the G7 countries combined, LE (LD) increased by 2.12 (0.25) and 2.73 (0.16) years for females and males, respectively. While most injury-related deaths contributed to increases in LE and decreases in LD, these gains were offset by negative contributions of unintentional poisoning, resulting in an overall negligible net contributions of injury deaths to changes in LE/LD across the G7 countries combined. The country-specific patterns revealed notable variations. Positive contributions of injury-related causes to changes in LE were more prominent in France (+ 0.38/+0.64 years for females/males), while negative contributions were most evident in the USA (-0.23/-0.42 years for females/males). Transport accidents emerged as the leading contributors to improvements in both LE and LD among both sexes in all countries, with more pronounced effects in males. In contrast, unintentional poisoning had a substantial negative impact, particularly among younger populations in the USA, UK, and Canada. Conclusion Injury deaths made negligible contributions to overall changes in LE and LD across the G7 countries combined during the study period. However, there were important variations by sex, age, cause and country. Specifically, unfavourable contributions of injury deaths were mainly observed in the USA, UK, and Canada. These findings highlight the need for targeted, country-specific injury prevention strategies to mitigate premature and unequal mortality.